Economic aspects of gender equality: results of marketing research - Borysova, Tetiana (Herald of Economics, 2022)
Introduction.The article presents the results of an empirical study conducted jointly with the Kyiv Institute for Gender Studies with the financial support of the Danish Ministry of Foreign Affairs in the framework of the project «Public assessment of the state of implementation of state documents on gender equality».The analysis of scientific works revealed a lack of research on the economic aspects of ensuring gender equality at the regional level in the context of COVID19.The aim of the article was to identify economic aspects of gender equality in the context of the implementation of the National Action Plan to implement the recommendations of the UN Committee on the Elimination of Discrimination against Women in Ternopil region.Research methods: analysis of secondary information; questionnaires; observation; personal interviews; method of comparative analysis; synthesis; generalization; grouping.Results. The study revealed the following: In the organizational structure of management of two of the three district state administrations the issue of gender policy is referred to the powers of other units, at the oblast level there is a department for family and gender policy, in one district this issue is transferred to JTT. At the district level, advisory advisory bodies and working groups on gender issues do not work at district state administrations. At the oblast level, there is a regional coordination council on the family, gender equality, prevention of domestic violence and combating trafficking in human beings. There are no gender advisers at the district level. At the oblast level, there is a gender adviser; Weak or no cooperation with women’s organizations or groups representing women with multiple discrimination at the district level. Very few recommendations of the National Plan have been implemented – 29 %. UAH 50,000 is provided only for the implementation of the first of the 4 recommendations. from the regional budget. The number of implemented measures of the National Plan amounted to 30 %, not all measures are included in the regulations adopted in the region, the budget was 0 UAH.Further research will focus on developing marketing strategies to promote gender equality at the regional level.